(untitled) (Baghdad Science Journal, 2011)
In this study, the chamomile flowers (Matricaria recutitaL) which grow in Iraqi Kurdistan region during the seasons of (2008) are collected. The percentage of essential oil was determined by using steam distillation and the extraction of flowers performed with petroleum ether (70-80) ºC and methanol 70% using ultrasonic extraction. Total phenolic compounds were determined from methanol extracts by using Folin-Ciocalteu method. The extracts were evaluated by thin layer chromatography, ultraviolet absorption and the biological activities were evaluated through their antibacterial action against two types of bacteria using hole method. The flowers showed a composition of 0.071% ash, 0.4% essential oil, 3.2% non oily compounds, 4% oil, 1.9% moisture and 0.19% total phenols. The results showed that the flowers contain biological active compounds and they can be used for treatment of diseases.